Fashion and Carnival: a creative approach (ModaPalavra e-periódico, 2015)
This study analyzes the creative process used in the production of a fashion collection and a parade for a carnival institution. The study uses creative techniques (methods) including brainstorming, brainwriting and the attribute listing. This study will also identify important aspects to be considered in the development of the both research.
Keywords: creativity; fashion; carnival